CT Scans in Young People in Great Britain: Temporal and Descriptive Patterns, 1993–2002 - Mark S. Pearce; Jane A. Salotti; Nicola L. Howe; Kieran McHugh; Kwang Pyo Kim; Choonsik Lee; Alan W. Craft; Amy Berrington de Gonzaléz; Louise Parker (Radiology Research and Practice)
Background. Although using computed tomography (CT) can be greatly beneficial, the associated relatively high radiation doses have led to growing concerns in relation to potential associations with risk of future cancer. Very little has been published regarding the trends of CT use in young people. Therefore, our objective was to assess temporal and other patterns in CT usage among patients aged under 22 years in Great Britain from 1993 to 2002. Methods. Electronic data were obtained from the Radiology Information Systems of 81 hospital trusts within Great Britain. All included patients were aged under 22 years and examined using CT between 1993 and 2002, with accessible radiology records. Results. The number of CT examinations doubled over the study period. While increases in numbers of recorded examinations were seen across all age groups, the greatest increases were in the older patients, most notably those aged 15–19 years of age. Sixty percent of CT examinations were of the head, with the percentages varying with calendar year and patient age. Conclusions. In contrast to previous data from the North of England, the doubling of CT use was not accompanied by an increase in numbers of multiple examinations to the same individual.